Visceral adipose tissue and osteoarthritis, a two-sample Mendelian randomized study - Zhang, Yinzhen; Wang, Yanpeng; Xu, Ji; Wang, Zhengyan; Zhao, Wenhai; Zhao, Changwei (Frontiers in Medicine, 2024)
Background The relationship between visceral adipose tissue and osteoarthritis is not clear. The purpose of our study was to explore the relationship between visceral adipose tissue and osteoarthritis. Methods We used a two-sample Mendelian randomization method to select single-nucleotide polymorphisms (SNPs) significantly associated with visceral adipose tissue as instrumental variables to explore the relationship between visceral adipose tissue and all osteoarthritis, hand osteoarthritis, hip osteoarthritis, knee osteoarthritis, and spine osteoarthritis. The reliability of the results was tested using sensitivity analysis. Results Our findings indicated that visceral adipose tissue was associated with all osteoarthritis, hip osteoarthritis, knee osteoarthritis, and spine osteoarthritis (all osteoarthritis: OR = 1.399, 95% CI: 1.335–1.467, p = 7.95e-44; hip osteoarthritis: OR = 1.399, 95% CI: 1.284–1.524, p = 1.41e-14; knee osteoarthritis: OR = 1.794, 95% CI: 1.662–1.937, p = 1.33e-50; and spine osteoarthritis: OR = 1.445, 95% CI: 1.314–1.589, p = 2.89e-14). Sensitivity analysis demonstrated the reliability of these results. Conclusion Our study suggests that genetically predicted visceral adipose tissue is associated with osteoarthritis. Reducing the accumulation of visceral adipose tissue could potentially have an impact on the incidence of osteoarthritis.